Anatomy of the Respiratory System and Heart of the Sloth (Choloepus hoffmanni) of Costa Rica - Vigil-Esquivel, Daira Jimena (2021)
The two-toed sloth (Choloepus hoffmanni) faces various diseases related to the respiratory and circulatory system. Thus, prior knowledge of anatomy becomes relevant since it contributes to the study and interpretation of medical images and surgical procedures. This study aims to describe the topographic and macroscopic anatomy of the heart and the respiratory system. Three animals were preserved with a supersaturated saline solution. Throughout the dissection, it was possible to identify and describe the components of the respiratory system and the heart. Some of the particularities found were the division of the frontal sinus in several sections. In addition, the presence of a large thyroid cartilage and the absence of wedge-shaped processes in the epiglottis were observed. The heart was small, although with very prominent auricles. These findings should be considered in the performance of clinical-surgical procedures and in the interpretation of medical images.